Lessons for public pensions from Utah's move to pension choice*. (10th June 2016) - CLARK, ROBERT L.; HANSON, EMMA; MITCHELL, OLIVIA S.
Abstract: We explore what happened when the state of Utah moved away from its traditional defined benefit pension. In its place, it offered new hires a choice between a conventional defined contribution plan and a hybrid plan option, where the latter has both a guaranteed benefit component and a defined contribution plan where employees bear investment risk. We show that around 60% of new hires failed to make any active choice and, as a result, were automatically defaulted into the hybrid plan. Slightly more than half of those who made an active choice elected the hybrid plan. Post-reform, employees who failed to actively elect a primary retirement plan were also far less likely to enroll in a supplemental retirement account, compared with new hires who actively selected a plan. We also find that employees hired following the reform were more likely to leave public employment, resulting in higher separation rates. This could reflect a reduction in the desirability of public employment under the new pension design and an improving economic climate in the state. Our results imply that public pension reformers must consider employee responses in addition to potential cost savings, when developing and enacting major pension plan changes.